Poets on Place - Pfefferle, W. T. (Utah State University, University Libraries, 2005)
Out to see America and satisfy his travel bug, W. T. Pfefferle resigned from his position as director of the writing program at Johns Hopkins University and hit the road to interview sixty-two poets about the significance of place in their work. The lively conversations that resulted may surprise with the potential meanings of a seemingly simple concept. This gathering of voices and ideas is illustrated with photo and word portraits from the road and represented with suitable poems.The poets are James Harms, David Citino, Martha Collins, Linda Gregerson, Richard Tillinghast, Orlando Ricardo Menes, Mark Strand, Karen Volkman, Lisa Samuels, Marvin Bell, Michael Dennis Browne, David Allan Evans, David Romtvedt, Sandra Alcosser, Robert Wrigley, Nance Van Winckel, Christopher Howell, Mark Halperin, Jana Harris, Sam Hamill, Barbara Drake, Floyd Skloot, Ralph Angel, Carol Muske-Dukes, David St. John, Sharon Bryan, Donald Revell, Claudia Keelan, Alberto Rios, Richard Shelton, Jane Miller, William Wenthe, Naomi Shihab Nye, Peter Cooley, Miller Williams, Beth Ann Fennelly, Natasha Trethewey, Denise Duhamel, Campbell McGrath, Terrance Hayes, Alan Shapiro, Nikki Giovanni, Charles Wright, Rita Dove, Henry Taylor, Dave Smith, Nicole Cooley, David Lehman, Lucie Brock-Broido, Michael S. Harper, C. D. Wright, Mark Wunderlich, James Cummins, Frederick Smock, Mark Jarman, Carl Phillips, Scott Cairns, Elizabeth Dodd, Jonathan Holden, Bin Ramke, Kenneth Brewer, and Paisley Rekdal.